2017
DOI: 10.1093/nar/gkx708
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of RNA templated end-joining by chlorella virus DNA ligase and a novel iLock assay with improved direct RNA detection accuracy

Abstract: Ligation-based nucleic acid detection methods are primarily limited to DNA, since they exhibit poor performance on RNA. This is attributed to reduced end-joining efficiency and/or fidelity of ligases. Interestingly, chlorella virus DNA ligase (PBCV-1 DNA ligase) has recently been shown to possess high RNA-templated DNA end-joining activity; however, its fidelity has not yet been systematically evaluated. Herein, we characterized PBCV-1 ligase for its RNA-templated end-joining fidelity at single base mismatches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…We anticipate that improvements in probe design algorithms might directly yield improvements in detection efficiency. While PBCV1 based direct RNA detection offers a high detection specificity, the overall fidelity needs to be further improved for applications pertaining to single nucleotide polymorphism detection, without compromising sensitivity 31 . We are actively working on improving In-situ sequencing read depth, read-length and improved basecalling algorithms with error-correction codes.…”
Section: Limitationsmentioning
confidence: 99%
“…We anticipate that improvements in probe design algorithms might directly yield improvements in detection efficiency. While PBCV1 based direct RNA detection offers a high detection specificity, the overall fidelity needs to be further improved for applications pertaining to single nucleotide polymorphism detection, without compromising sensitivity 31 . We are actively working on improving In-situ sequencing read depth, read-length and improved basecalling algorithms with error-correction codes.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, DNA ligation assays perform much better on DNA substrates than on RNA substrates (Nilsson et al 2000). Most DNA ligases do not tolerate RNA templates, and the ones that do, for example, Chlorella virus DNA ligase (PBCV-1 DNA ligase), have poor end-joining fidelity (Krzywkowski and Nilsson 2017). We have recently improved the end-joining fidelity of PBCV-1 ligase on RNA by adopting the highly specific nucleic acid sensing property of Taq DNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of SCRINSHOT crucially relies on the specific targeting of the SplintR ligation activity to the correct sites of the interrogated mRNA. A recent study (33) reported that the fidelity of this ligase is poor as it tolerates mismatches at padlock probe junctions. In addition, SplintR shows 1% of its ligation activity on a 1-nucleotide gap of a nicked duplex DNA substrate and it is unable to join ends across a 2-nucleotide gap (35).…”
Section: Resultsmentioning
confidence: 99%
“…Not hybridized padlock probes were removed by washes with 10% Formamide in 2X SSC (Sigma-Aldrich, S6639). To minimize the effect of the previously documented SplintR ligase nucleotide preferences (26, 33), padlock probe ligation was performed overnight O/N at 25°C using the SplintR ligase (NEB, M0375) at a final concentration of 0.5 Units/μl, T4 RNA ligase buffer (NEB, B0216) and 10μM ATP, according to manufacturer recommendations (see New England Biolabs webpage).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation